2016
DOI: 10.1515/acs-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of curcuminoids isolated from Curcuma longa L.

Abstract: The evaluation of antioxidant potential of food has received much attention in recent years. Antioxidant compounds can scavenge free radicals and thereby can protect the human body from free radicals. This study was focused on the isolation of curcuminoids from the dried turmeric rhizome, and studying their antioxidant activity. The presence of curcuminoids was identified in turmeric sample by Nuclear Magnetic Resonance (NMR) analysis. Since neutral curcumin is known to be poorly soluble, the synthesis of curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…This chemical structure makes curcumin less soluble in water at acidic and neutral pH but soluble in ethanol, alkali, ketone, methanol, acetic acid, and chloroform, dimethyl sulfoxide (DMSO), and acetone. The melting temperature of curcumin is 176-177°C (Mosǒvskáet al, 2016) and it has various methoxy substitutions in the diferuloylmethane chemical structure (which is responsible for yellow coloration), demethoxycurcumin, bisdemethoxycurcumin, and cyclocurcumin ( Figure 1) are responsible for many biological and pharmacological differential activities of these compounds (Anand et al, 2008). Somparn et al reported that diferuloylmethane shows better antioxidant activity than demethoxycurcumin and bisdemethoxycurcumin, and demethoxycurcumin to have a potent antioxidant effect than bisdemethoxycurcumin (Somparn et al, 2007).…”
Section: Chemical Structure and Molecular Targets Of Curcuminmentioning
confidence: 99%
“…This chemical structure makes curcumin less soluble in water at acidic and neutral pH but soluble in ethanol, alkali, ketone, methanol, acetic acid, and chloroform, dimethyl sulfoxide (DMSO), and acetone. The melting temperature of curcumin is 176-177°C (Mosǒvskáet al, 2016) and it has various methoxy substitutions in the diferuloylmethane chemical structure (which is responsible for yellow coloration), demethoxycurcumin, bisdemethoxycurcumin, and cyclocurcumin ( Figure 1) are responsible for many biological and pharmacological differential activities of these compounds (Anand et al, 2008). Somparn et al reported that diferuloylmethane shows better antioxidant activity than demethoxycurcumin and bisdemethoxycurcumin, and demethoxycurcumin to have a potent antioxidant effect than bisdemethoxycurcumin (Somparn et al, 2007).…”
Section: Chemical Structure and Molecular Targets Of Curcuminmentioning
confidence: 99%
“…Curcumin significantly inhibits the peroxidation of lipids in various animal models (Maheshwari et al, 2006). Metabolism of lipoxygenase (LOX), arachidonic acid, and cyclooxygenase (COX) inhibited by the curcumin, which alters the productions of steroidal hormones (Mosovska et al, 2016). Researchers have investigated the antioxidant property of curcumin in animal cells by exposing the oxygen and nitrogen-free radical species and concluded the antioxidant efficacy of curcumin (Rafiee et al, 2019).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Their scavenging activities against a variety of reactive oxygen species including superoxide anion radicals and nitrogen dioxide radicals are predominant. They are also inhibitors of lipid peroxidation in different animal models [14].…”
Section: Chemical Constitutesmentioning
confidence: 99%